Understanding the social in a social-ecological system: a perceptions study on the Diep River estuary, Cape Town - Wise, Carly (Department of Environmental and Geographical Science, 2023)
Our ever-urbanising world has seen a rift form between humans and the natural environment. Nature is readily displaced in pursuit of development, despite the critical dependence of people on nature's benefits. The field of urban ecology addresses this challenge by re-integrating the natural and social sciences, bridging the gap in our understanding of how society interacts with nature in an urban context. There are areas in cities where these interactions and relationships between society and nature are extremely complex, with interlinking and interdependent social and ecological dimensions. One approach to grasping the complexities of human-nature interactions is to view them as social-ecological systems (SESs). The SES perspective reveals key links between the social and ecological dimensions that would otherwise be overlooked if studied separately. Natural spaces in cities play an important role in providing multiple benefits to urban citizens and to the environment. But with urban nature under threat of loss and degradation, ecosystem services can be lost too. The Diep River estuary in Cape Town is an important system from both a social and an ecological perspective. However, there has been a significant decline in the state and health of the system. While the Diep River estuary boasts decades of meticulous ecological research, little is known or written about the ways in which urban citizens use, perceive and value this natural resource. This suggests that the estuary has historically not been viewed as a system with interconnected social and ecological dimensions. To address this gap, this study examined people's perceptions of the Diep River estuary, both in the moment and through time, to gain a deeper understanding of the social dimension of the Diep River estuary SES. Following a predominantly interpretive case-study approach, historical data associated with the estuary were analysed to reveal changes in estuary use over time. Forty-five questionnaire surveys and seven key-informant interviews were conducted to gather deep insights and narratives from every-day as well as long-term estuary users. Findings from this research illustrated a deep sense of place relating to the estuary, which encouraged pro-environmental behaviour and a ubiquitous awareness of the estuary's state. There was also a clear relationship between the regularity of use of this urban estuary and local residents, highlighting the importance and relevance of accessibility to nature in urban spaces. The research suggests that the public hold valuable insights and deep understandings of natural systems, and effective ecosystem management should incorporate stakeholder understanding and perceptions. Furthermore, environmental stewardship can be cultivated through strategic urban planning that ensures access to natural urban spaces, encouraging their protection and the future sustainability of their benefits.